Scientific and Methodological Basics of Formation of Preschoolers’ Readiness for Social and Personal Orientation - V. Barcaeva, E.; V. Ryabova, N.; V. Zolotkova, E. (International Journal of Engineering and Technology, 2018)
The article deals with the theoretical justification and development of a model of the formation of readiness for social and personal orientation of preschoolers, as well as the evaluation of the pedagogical conditions of such formation. The leading approaches to studying the problem are the social and cultural approach, the system approach, the activity approach, and the anthropological approach that constitute the theoretical and methodological basis of the readiness under consideration.The article presents the theoretical review of the literature related to the problem of formation of readiness for social and personal orientation of preschoolers at additional education institutions. The definitions of the following terms are given: "social and personal orientation", "readiness for social and personal orientation of preschoolers", and "formation of readiness for social and personal orientation of preschoolers". The article describes the main components of the structure of readiness for social and personal orientation of preschoolers – personal, cognitive, and activity components. The model of the formation of readiness for social and personal orientation of preschoolers at additional education institutions is elaborated. The main components of the model – theoretical and methodological, target, content, process, and resultative and evaluative – are presented and characterized in detail. The pedagogical conditions of implementing the model are justified and tested. The results of the summative and formative assessment and the control experiment are presented and analyzed. The pilot testing was carried out at additional education institutions in Saransk, Republic of Mordovia. The theoretical analysis of the literature on the topic and the empirical methods have been used in the research.The relevance of the research aimed at studying readiness for social and personal orientation of preschoolers at additional education institutions is defined by the fact that the obtained results contribute to the successful social orientation of children of this category in society.